KUALITAS ARANG ENAM JENIS KAYU ASAL JAWA BARAT SEBAGAI PRODUK DESTILASI KERING - Novitri Hastuti; Gustan Pari; Dadang Setiawan; Mahpudin; Saepuloh (BRIN Publishing, 2015)
Six wood species from West Java which are ki hiur (Castanopsis acuminatissima A.DC.), tunggeureuk (Castanopsis tunggurut), huru pedes (Cinnamomum iners Reinw.Ex Bl.), huru koja (Litsea angulata Bl.), ki kanteh (Ficus nervosa Heyne) and kelapa ciung (Horsfieldia glabra Warb) have been distillated by dry distillation at temperature 450°C-500°C for five hours in the retort distillation. Distillates from the dry distillation in form of charcoal, tar and liquid are calculated. The results exhibited charcoal quality of six woods meet the standards of Indonesia for charcoal and charcoal briquettes with calorific values ranging from 6743-6795 cal/g, fixed carbon ranging from 79.42 % - 82.37 %. Charcoal yield ranging from 27.43 % -33.55 % . Pearson correlation analysis on the lignin content and woodgravity to charcoal calorific value indicates that the lignin content has a significant correlation to the calorific value of charcoal.